MENGANALISIS PENYEBAB KEPUTUSAN PEDAGANG UMKM KOTA SUMBAWA DALAM MENGGUNAKAN QRIS SEBAGAI MEDIA TRANSAKSI KEUANGAN - Muhammad Nur Fietroh (Pusat Riset dan Publikasi, 2023)
This study aims to analyze the factors that influence traders' decisions to use QRIS in Sumbawa Regency. This study used an associative method with a quantitative approach. The sample in this study consisted of 100 respondents obtained using the nonprobability sampling method. Data were analyzed using multiple regression analysis, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and coefficient of determination testing (R2) using the SPSS application. Based on the partial test results, it can be concluded that the Social Influence and Business Expectations variables have a positive and significant effect on the decision to use QRIS as a financial transaction medium, while the hedonistic motivation and habits variables do not have a significant effect on the decision to use QRIS as a financial transaction medium. Meanwhile, the results of simultaneous testing show that together the Social variables, Hedonistic Motivation, Habits and Business Expectations have a significant influence on the decision to use QRIS as a financial transaction medium. The independent variables consisting of the Social Influence, Hedonistic Motivation, Habits, and Business Expectations ariable had an influence on the decision to use QRIS variable was 73%, while the remaining 27% is influenced by other variables not examined in this research.